Muscular Strength Spurts in Adolescent Male Basketball Players: The INEX Study - Guimarães, Eduardo (Int J Environ Res Public Health, 2021)
Although successful performance in basketball requires high levels of muscular strength during adolescence, its development is confounded by the effects of normal growth. We examine the timing, intensity and sequence of muscular strength according to biological age (years from peak height velocity (PHV)) and hypothesize that young basketball players attain their peak muscular strength spurts around PHV. A total of 160 adolescent male basketballers, aged 11–15 years, were followed bi-annually over 3 consecutive years. The years from attainment of PHV and peak weight velocity (PWV) were estimated and five muscular strength measures (sit-ups, handgrip, seated medicine ball throw, squat jump and countermovement jump) were aligned to years from PHV in 3-month intervals. Strength velocities were estimated using a non-smooth mathematical model. The mean ages at-PHV and at-PWV were 13.90 ± 1.40 years and 13.90 ± 1.79 years, respectively. Maximal velocity in sit-ups was attained 6 months prior to attainment of PHV (intensity = 10.69 repetitions·year(−1)), whereas maximal velocity in squat jump occurred 6 months after-PHV (intensity = 3.93 cm·year(−1)). Handgrip strength, seated medicine ball throw and countermovement jump maximal velocity peaked at-PHV (intensity = 8.47 kgf·year(−1), intensity = 0.75 m·year(−1), intensity = 5.59 cm·year(−1), respectively). In general, maximal velocity spurts did not differ in their timing, with the velocities reaching a peak concurrent with PHV and PWV or within 6 months of its attainment. Basketball coaches, as well as strength and conditioning trainers, should consider individual differences in strength development and be aware of rapid periods of growth in stature when planning and designing muscular strength training regimes.